Earthquake and structural monitoring system (ensms) [electronic resource] - 220629 Raja Norasyikin Raja Ali; Safie Mat Yatim, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2008